Isolation and characterization of thermostable protease producing bacteria from tannery industry effluent - R. Philip, N. Kannan, T. R Srinivasan, S. Das, V. Balakrishnan (Recent Research in Science and Technology, 2009)
The Ã‚Â study is a search for potential thermostable protease producing strains from tannery industry effluent. Among nine protease producing strains screened, one was selected as promising thermostable protease producer and identified as Bacillus sp. The activity of the protease produced by this organism is stable up to 700C. The optimum yield was achieved after 48 hours of culture, at 600C with the pH 8.0. The desired protein was precipitated from the crude extract by using ammonium sulfate (70%) followed by dialysis and purified by Ion-exchange chromatography. The maximum protease activity was observed at 650C and at pH 8.0. Further investigation on structure elucidation to this purified protein Ã‚Â for industrial level exploitation is in progress.